Frihedsretorik og totalitære tendenser. Sand oplysning og danskhed hos Grundtvig - Harbsmeier, Eberhard (Grundtvig-studier, 2001)
Freedom rhetoric and totalitarian tendencies.True information and Danishness at Grundtvig By Eberhard Harbsmeier